Management of Humeral Fracture in a Dog at Klinik Bersama Dokter Hewan Jungle Bekasi - Toni Aditya Prayoga; Panggabean, Rudi H.; Rickyawan, Nofan (Faculty of Veterinary Medicine Universitas Brawijaya, 2023)
A humeral fracture is a discontinuity of the humeral bone due to an injury or illness. A three-year-old black mongrel female dog weighing 12.5 kg was brought to the Jungle Veterinary Clinic in Bekasi City, Indonesia, due to lameness and swelling in the left front limb. The radiological examination indicated an oblique fracture of the distal diaphysis of the left humerus. Haematological and biochemistry tests indicated neutrophilia, leukocytosis, and decreased erythrocyte, haemoglobin, hematocrit, MCV and MCH levels, while the levels of globulin and ALP were elevated. An orthopaedic surgery was performed using cerclage wires in conjunction with the intramedullary pin approach to immobilize the fracture. Post-surgery medical treatments were oral Amoxicillin 20 mg/kg, tramadol 5 mg/kg, meloxicam 0.1 mg/kg, Curcuma™ ½ tablet, Sangobion™ ½ tablet, and Kalmicetin™ ointment for topical wound dressing twice a day. The surgical wound healed and front leg function improved seven days after surgery